The Role Of Public Health Surveillance In Strengthening Health Security (The Review of Diabetic Studies, 2025)
BackgroundPublic health surveillance involves the systematic collection, analysis, interpretation, and dissemination of health data to inform actions against threats like pandemics and bioterrorism, integrating with frameworks such as the International Health Regulations (IHR) and Global Health Security Agenda (GHSA) to enhance global resilience.​ Surveillance tracks disease trends, detects outbreaks early, and supports evidence-based policies amid globalization's risks, where travel amplifies threats, as seen in historical gaps during epidemics.​MethodsThis narrative review synthesizes peer-reviewed literature, case studies (Ebola, COVID-19, Zika, mpox), and real-world data from diverse global contexts, evaluating surveillance typologies, innovations like digital tools and wastewater monitoring, and frameworks including One Health and IHR core capacities.​ResultsCase studies reveal surveillance strengths in early detection (e.g., wastewater providing 6-8 day leads for COVID-19) but gaps like underfunding, data silos, and LMIC workforce shortages prolonging outbreaks (e.g., Ebola's 28,000+ cases); innovations such as AI prediction (>94% accuracy) and genomic networks mitigate these.​ConclusionsRobust, equitable surveillance is essential for health security; recommendations include AI integration, interoperable global platforms, LMIC capacity-building, and climate-adaptive strategies to preempt emerging threats.​